ANALISIS PROFIL KONDIDI FISIK ATLET ATLETIK NOMOR LEMPAR CLUB PAS KOTA SALATIGA 2026 - Galih Yoga Widya Utama; Dani Slamet Pratama; Galih Dwi Pradipta (YLPK Mahardhika, 2026)
This study aims to describe the physical condition profile of throwing event athletes at PAS Club Salatiga City in 2026. The research employed a descriptive quantitative method with a total sampling technique involving 10 athletes. Data were collected using standardized physical condition tests covering five components: speed, muscle strength, agility, flexibility, and explosive power. The results showed that 50% of athletes were in the moderate category, 30% in the very good category, and 20% in the good category, with no athletes categorized as poor or very poor. These findings indicate that, in general, the athletes’ physical condition is adequate but not yet optimal and unevenly distributed. Therefore, improvements are needed through more structured, systematic, and continuous training programs to enhance overall physical performance. This study highlights the importance of regular evaluation to support athlete development and performance improvement.